Spatial distribution of recreational services in the city of Essaouira - Assist. Prof. . Khaled Jawad Salman Al-Shammari (Journal of College of Education, 2024)
The field study seeks to know the reality of the spatial distribution of entertainment services in the city of Essaouira and to find out the reasons for its variation between residential neighborhoods in accordance with the approved local planning standards. The field study included a questionnaire form, field visits and personal interviews with departments related to the study of the city, a map of the study area and a number of tables and graphs were drawn and the distribution of recreational services using the criteria of degree of satisfaction and ease of access and using the Pearson correlation coefficient through the study, the poor distribution of recreational services in residential neighborhoods and variation in their numbers from one place to another was revealed. The study concluded that the city suffers from a shortage in the number of recreational services and their poor distribution where they are concentrated in one place, and it is less or non-existent in another part of the city’s neighborhoods, failure to take into account the planning standards in its distribution with the needs of the population, which is constantly increasing. It is represented by residents of Essaouira who go to various types of recreational services, including public gardens, parks, playgrounds for children and youth, sports stadiums, clubs, cinemas, theatres, museums and youth centres. Linked to this list are some services such as hotels, cafes and restaurants, which they resort to in search of quiet and enjoyable places away from the noisy city life. It also gives cities an aesthetic appearance that is comfortable for the soul and brings joy and happiness to them.
Keywords: recreational services, planning standards, physical comfort, public parks, museums.